First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana - Moratelli, Ricardo (Biodivers Data J, 2015)
Abstract. BACKGROUND: Myotis albescens occurs from Mexico southward to Uruguay and Argentina. The species is known for all South American countries except French Guiana and Chile. NEW INFORMATION: Based on one specimen recently collected in French Guiana we fill part of the gap in the distribution of the species in South America. Myotis albescens occurs in the Guiana Shield with other four congeners, from which it can be distinguished by external and skull traits. As an aid to future identifications, we provide a key to this assemblage.